Prognostic Implications of Pyroptosis-Related Gene Signatures in Lung Squamous Cell Carcinoma - Li, Tingting; Liu, Huanqing; Dong, Chunsheng; Lyu, Jun (Frontiers in Pharmacology, 2022)
Background: Lung squamous cell carcinoma (LUSC) is a highly malignant tumor with very poor prognosis. Pyroptosis has recently been confirmed as an inflammatory form of programmed cell death. However, the correlation between the expression of pyroptosis-related genes and their prognosis remains unclear in LUSC. Methods: The Cancer Genome Atlas (TCGA) cohort was used to evaluate the prognostic value of these genes on the survival and to construct a multi-gene signature. The least absolute shrinkage and selection operator (LASSO) Cox regression and Cox regression were performed to establish the pyroptosis-related gene signature. Results: A total of 28 pyroptosis-related genes that were differentially expressed between the LUSC and normal lung tissues were identified. Based on these differentially expressed genes, all patients with LUSC were divided into two subtypes. Nine gene signatures were established using LASSO, and all patients with LUSC in the TCGA cohort were divided into low-risk and high-risk groups. The survival rate was significantly higher in the low-risk group than in the high-risk group (P <0.001). Combined with the clinical characteristics, the risk score was found to be an independent predictor of the overall survival time in the patients with LUSC. Results from the Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analyses showed that immune-related genes were enriched and immune status decreased in the high risk group. Conclusion: Pyroptosis-related genes played an important role in tumor immunity and could be used to predict the prognosis of LUSCs.